Comparative Studies on the Isolation of Membrane Lipoteichoic Acid from Lactobacillus fermenti - Wicken, A. J. (1973)
Preparations of membrane lipoteichoic acid containing different amounts of protein were isolated from intact organisms of Lactobacillus fermenti NCTC 6991 by various procedures chosen for their ability to disrupt the hydrophobic interaction of lipoteichoic acid with other membrane components. The highest yield of lipoteichoic acid was obtained with hot aqueous phenol, and this preparation contained very little protein. Partial removal of cell lipids with chloroform-methanol followed by extraction with water at 100 C gave a lipoteichoic acid-protein complex that was a very effective immunogen; immunogenicity was shown to relate to protein content, though the specificity of the antibodies was directed against the teichoic acid component.